2017
DOI: 10.5301/jabfm.5000383
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of corrosion resistance of cast cobalt- and nickel-chromium dental alloys in acidic environments

Abstract: Ni-Cr alloys are unstable in solution and leach nickel. Co-Cr alloys should be preferred for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 17 publications
0
19
0
2
Order By: Relevance
“…Nickel exposure is associated with a number of systemic disorders. 4 In case of metal contact allergy, exposure to dental crowns could play a role. 5 Allergens can leach from an alloy and dissolve in the oral environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nickel exposure is associated with a number of systemic disorders. 4 In case of metal contact allergy, exposure to dental crowns could play a role. 5 Allergens can leach from an alloy and dissolve in the oral environment.…”
Section: Introductionmentioning
confidence: 99%
“…Mercieca studied the corrosion resistance of cast cobalt‒ and Ni‒Cr dental alloys in acidic saliva and concluded that Ni‒Cr alloys are unstable in solution and leach Ni ions. 4 The use of mouthwashes containing fluoride, chloride or essential oils is occasionally recommended by prosthodontist as an adjunctive therapy to reduce the risk of caries and plaque formation and overcome periodontal conditions, such as gingivitis. 11 However, only a limited number of studies have investigated the relationship between mouthwashes and metal corrosion of Ni‒Cr alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Based on experimental data, it was established that thermal reprocessing effects lead to the enhancement of commonly used dental commercial alloys and their demerits regarding corrosion and biocompatibility [17]. As an example, recasting of alloys increased cytotoxicity level including ion release from NiCr and CoCr alloys; CoCr alloys were more adversely affected by the recasting than the NiCr alloys [18]. Regarding electrochemical stability after reprocessing in various environments, a decrease in corrosion rate common for both types of alloys NiCr and CoCr, respectively, was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt-chromium-based alloys (Co-Cr alloy) are widely used for the fabrication of removable partial dentures and metal ceramic prostheses [16]. Co-Cr alloy exhibits high strength, good cytocompatebility and are nonmagnetic [17,18]. Additionally, Co-Cr alloys have also been found to be more resistant to corrosion than Ni-Cr alloys [16,18].…”
Section: Introductionmentioning
confidence: 99%
“…Co-Cr alloy exhibits high strength, good cytocompatebility and are nonmagnetic [17,18]. Additionally, Co-Cr alloys have also been found to be more resistant to corrosion than Ni-Cr alloys [16,18]. These properties make Co-Cr ideal alloys to be used in the oral cavity [16].…”
Section: Introductionmentioning
confidence: 99%